2020
DOI: 10.1186/s12876-020-01415-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical outcomes between isolated pancreaticojejunostomy, isolated gastrojejunostomy, and conventional pancreaticojejunostomy after pancreaticoduodenectomy: a systematic review and meta-analysis

Abstract: Background: We aimed to compare the safety and effectiveness of the following procedures after pancreaticoduodenectomy: isolated pancreaticojejunostomy, isolated gastrojejunostomy, and conventional pancreaticojejunostomy. Methods: We performed a systematic search of the following databases: PubMed, Embase, Web of Science, the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov until 1 January 2020. Pooled odds ratios (OR) or weighted mean differences (WMD) with 95% confidence intervals (CIs)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…The technique proposed by Aghalarov does not influence the rate of POPF, but reduced its severity, leading to less major morbidity and mortality. More recently, Lyu et al 26 reported a systematic review and meta-analysis comparing isolated PJ, isolated gastro-jejunostomy, and conventional PJ after PD. The results of this meta-analysis showed that isolated PJ was associated with a lower reoperation rate, but required longer operation time vs conventional PJ.…”
Section: Discussionmentioning
confidence: 99%
“…The technique proposed by Aghalarov does not influence the rate of POPF, but reduced its severity, leading to less major morbidity and mortality. More recently, Lyu et al 26 reported a systematic review and meta-analysis comparing isolated PJ, isolated gastro-jejunostomy, and conventional PJ after PD. The results of this meta-analysis showed that isolated PJ was associated with a lower reoperation rate, but required longer operation time vs conventional PJ.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many methods for the prevention and treatment of pancreatic fistula after pancreaticoduodenectomy, such as drug prevention, improvement of surgical methods and preoperative reduction of yellow, etc. [16][17][18][19][20][21], these methods cannot completely prevent the occurrence of pancreatic fistula and biliary fistula. Therefore, this study attempted to divide the patients into two groups, A and B, according to the different sites of gastric tube implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Die Anastomosierung von Restpankreas, Gallengang und Magen/Duodenum an dieselbe Schlinge ist aufgrund der relativ einfachen Technik und basierend auf der aktuellen Datenlage als Standardrekonstruktion anzusehen [ 56 , 57 ]. So bringt die Durchführung von Pankreas- und Gallengangsanastomose in getrennt ausgeschalteten Schlingen keinen nachweisbaren Nutzen und ist aufgrund des größeren technischen und zeitlichen Aufwandes nicht zu empfehlen [ 58 ].…”
Section: Onkologische Resektion Und üBerlebenunclassified